Indonesia Defence Diplomacy To Make Tanjung Datu Segment As Outstanding Boundary Problem Of Indonesia-Malaysia - Istiqamah, Istiqamah (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract – This study discusses about implementation of Indonesia’s defense diplomacy and its analysis in effort to obtain Tanjung Datu segment as Outstanding Boundary Problem of Indonesia-Malaysia. This is based on the status of Tanjung Datu as Outstanding Boundary Problem was ambiguous due the different interpretations of Memorandum of Understanding (MOU) 1976 and 1978 by Government of Indonesia. The negotiation to obtain Tanjung Datu segment as Outstanding Boundary Problem Indonesia-Malaysia in 2001. Indonesia attempt to lobby Malaysian to attach Tanjung Datu as OBP and its intensively conducted by Indonesia’s delegates until finally, Indonesia accepted the Malaysian decision that Tanjung Datu is not part of the OBP. This research method was qualitative approach where data collection technique was through interviews with six informants including practitioners and experts in related fields. This study showed that the subjects of Indonesia’s defense diplomacy in efforts to obtain Tanjung Datu segment as OBP Indonesia-Malaysia are Pankorwilnas, Directorate of Army Topography, Ministry of Defense, Ministry of Home Affairs and JUPEM (Malaysian Position Measurement and Mapping). While the object of Indonesia’s defense diplomacy in the efforts to obtain Tanjung Datu segment as OBP Indonesia-Malaysia are the implementation of Indonesia’s national interest to achieve territorial sovereignty and it was also part of defense. Keywords : Defense Diplomacy, Bounday Making Theory, Territorial Sovereignty, Tanjung Datu Segment, Outstanding Boundary Problems.